AB0792 Changes in the Metabolism of Hyaluronan Are Associated with Inflammatory Cytokines in Patients with Ankylosing Spondylitis. (9th June 2015) - Hellman, U.; Hedqvist, D.; Do, L.; Sundström, B.; Wållberg-Jonsson, S.
Abstract : Background: Hyaluronan (HA) is a glucosaminoglycane, mainly known for its lubricating and shock absorbing properties in joints, present in almost every tissue in the body. An association was recently reported between the concentration of HA and back stiffness in patients with ankylosing spondylitis (AS). Depending on the molecular size, HA also has different inflammatory properties. Objectives: The aim of this study was to analyze plasma levels of HA in patients with AS and a reference population to evaluate any difference between the groups regarding HA concentration and/or molecular weight of HA molecules. In the AS group, these results were related with variables reflecting inflammation and stiffness. Methods: In a cohort of 66 patients (51 males, 15 females, mean age 47.7 years) with AS and a matched reference population of 30 controls, HA concentration was determined using enzyme-linked immunosorbent assay (ELISA). Subgroups comprising in all 30 patients and eleven controls were selected with respect to inflammatory status and stiffness. These subgroups were analysed for HA molecular weight using gas-phase electrophoretic molecular mobility analysis (GEMMA). In the patient group, the HA results were related to inflammatory variables (ESR, hsCRP, ASDAS, cytokines), functional disease activity (BASDAI) and back stiffnes according to a BASFI, question 8 ("looking over the shoulder without turning the body"). Results: No difference was found between the groups regarding HA total concentration (p=0.77). However, when assessing the molecular weight with GEMMA, a relative increase of high molecular weight (HMW) HA was found compared to low molecular weight (LMW) HA. HMW HA (GEMMA peak 4) increased with a fold change of 2.4 (p<0.02). The levels of a group of cytokines, TNF-α, IL-6, IL-17 and IFN-γ, were well correlated in the AS patients (p<0.05-0.0001). The levels of TNF-α and IL-6 also correlated with the relative increase of HMW HA (peak 4), compared to LMW HA. No significant correlations could be found between HA and the functional or stiffness status of the patients. Conclusions: The correlation of the levels of inflammatory markers with changes in the HA metabolism may indicate an association of HA with the disease process in AS. Furthermore, HA showed a link to inflammatory processes via TNF. The significant correlation found among the patients between the concentrations of HA of a certain molecular weight and TNF-α is challenging, since TNF-α inhibitors are used successfully in the treatment of AS. However, the patients' estimation of their stiffness could not be related to the molecular analyses. Disclosure of Interest: None declared